2023
DOI: 10.21203/rs.3.rs-3538792/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intravenous Vitamin C Supplementation in Allogeneic Hematopoietic Cell Transplant Recipients: Salutary Impact on Clinical Outcomes

Amir Toor,
Gary Simmons,
Roy Sabo
et al.

Abstract: Intravenous (IV) vitamin C improves organ function and reduces inflammation in sepsis, an inflammatory state like the post-hematopoietic stem cell transplant (HCT) milieu. The safety and efficacy of parenteral vitamin C after allogeneic HCT were evaluated in a phase I/II trial. Clinical outcomes were compared with a propensity score - matched historical control. Methods: Patients with advanced hematologic malignancies received IV vitamin C, 50mg/kg/d, divided into 3 doses given on days 1-14 after HCT, followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Since supplementation with Asc rescued the abnormality of the Akr1a-KO mice to an extent similar to that in the WT mice (Figure 1), we assumed that Asc either protected the BMCs from oxidative damage or stimulated the hematopoietic process. In fact, a recent clinical study has reported that intravenous administration of Asc (50 mg/kg/day, divided into three doses given on days 1-14) to patients undergoing allogeneic HSC transplant is safe and reduces non-relapse mortality, resulting in the improvement of overall survival [37]. The intravenous administration of mesenchymal stem cells overexpressing extracellular superoxide dismutase (SOD3) to the mice after 9-Gy γ-ray irradiation reportedly improved their survival [38].…”
Section: Discussionmentioning
confidence: 99%
“…Since supplementation with Asc rescued the abnormality of the Akr1a-KO mice to an extent similar to that in the WT mice (Figure 1), we assumed that Asc either protected the BMCs from oxidative damage or stimulated the hematopoietic process. In fact, a recent clinical study has reported that intravenous administration of Asc (50 mg/kg/day, divided into three doses given on days 1-14) to patients undergoing allogeneic HSC transplant is safe and reduces non-relapse mortality, resulting in the improvement of overall survival [37]. The intravenous administration of mesenchymal stem cells overexpressing extracellular superoxide dismutase (SOD3) to the mice after 9-Gy γ-ray irradiation reportedly improved their survival [38].…”
Section: Discussionmentioning
confidence: 99%